(untitled) (International Journal of Engineering and Computer Science, 2015)
JPEG is widely used method for image compression. JPEG image compression involves a sequence of steps in which quantization process plays a major role in compression process. Quantization table decides the quality of the encoded image and also controls the amount by which image should be compressed (compression ratio). Hence generation of quantization table in the JPEG baseline algorithm is viewed as an optimization problem. For the past few decades, numerous researches have been conducted to generate optimal Quantization table for a given image and they are categorized as follows; Rate-distortion approach, Human Visual System approach and Meta-Heuristics approach. In this paper, an extensive survey is made on these methods to generate optimized quantization table for the JPEG baseline algorithm